Indonesian Government Policies Supporting the Millennial Generation Amid the COVID-19 Pandemic - Ramadhan, M. Khablul Fajar (KnE Social Sciences, 2022)
Badan Pusat Statistik (BPS) has predicted that Indonesia will experience a substantial change in demographics by 2035. This is amid the COVID-19 situation, which has had a large impact on the economic, social and political sectors, and has had extensive consequences for the Millennial generation. According to recent data, 52% of those in the United States who have lost their jobs during the pandemic were aged less than 45 years, and only 25% of them were aged over 45 years. This shows that the group most affected by the COVID-19 pandemic has been the Millennial generation. Indonesia’s Millennial generation also faces challenges in dealing with the impact of the COVID-19 pandemic. This research was a literature study. The policies of the Indonesian government were an important variable in the impact of the COVID-19 pandemic on the Millennial generation. Keywords: COVID-19 pandemic, Indonesian government, Millennial generation